Sosialisasi Pemanfaatan Rumah Potong Hewan (RPH) di Kabupaten Batu Bara Provinsi Sumatera Utara - Yusni K. Tampubolon; Winda F. Saragih; Ma’ruf Tafsin; Nevy D. Hanafi; Achmad Sadeli (Lembaga Pengembangan Kinerja Dosen, 2025)
The community service activity was carried out in Lima Puluh Subdistrict, Batu Bara Regency. The partner in this activity was the Regional Development Planning, Research, and Development Agency. The main problem faced by the partner is the absence of an official slaughterhouse building in Batu Bara Regency. Until now, only independently managed slaughterhouses owned by the community have been used as animal slaughtering facilities. However, these slaughterhouses can only accommodate a limited number of slaughters. Moreover, issues related to poor meat hygiene and cross-contamination during slaughtering and packaging processes for consumer distribution are still frequently encountered. The solution to this problem is to establish an official slaughterhouse in Batu Bara Regency that meets both administrative and technical requirements. The purpose of this activity is to provide understanding to the community and stakeholders regarding the utilization of an official slaughterhouse and the importance of having a standardized slaughterhouse. The expected outcomes of this community service activity are: (1) to increase public knowledge in Batu Bara Regency regarding the importance of RPH utilization, (2) to enhance awareness of providing meat that is Safe, Healthy, Whole, and Halal (ASUH), and (3) to provide recommendations to the local government regarding the planning and development of an official slaughterhouse.